2019
DOI: 10.1039/c8nr09467e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing charge transport in an organic photoactive layer via vertical component engineering for efficient perovskite/organic integrated solar cells

Abstract: Efficient perovskite/organic integrated solar cells were fabricated via vertical component engineering to enhance charge transport in an organic photoactive layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…Wang et al constructed an organic bulk heterojunction (BHJ) network containing organic donor (PBDB-T) and acceptor (IEICO) as HTL of perovskite solar cells. [87] The distribution of organic donor and acceptor in the HTL was investigated using ToF-SIMS. ToF-SIMS results (Figure 11e-h) indicate that the donor-acceptor network is the vertical stratification in the PBDB-T:IEICO = 1:1 HTL film (device 1) and is bicontinuous in the PBDB-T:IEICO = 1:0.7 film (device 2).…”
Section: Htlmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al constructed an organic bulk heterojunction (BHJ) network containing organic donor (PBDB-T) and acceptor (IEICO) as HTL of perovskite solar cells. [87] The distribution of organic donor and acceptor in the HTL was investigated using ToF-SIMS. ToF-SIMS results (Figure 11e-h) indicate that the donor-acceptor network is the vertical stratification in the PBDB-T:IEICO = 1:1 HTL film (device 1) and is bicontinuous in the PBDB-T:IEICO = 1:0.7 film (device 2).…”
Section: Htlmentioning
confidence: 99%
“…ToF-SIMS results (Figure 11e-h) indicate that the donor-acceptor network is the vertical stratification in the PBDB-T:IEICO = 1:1 HTL film (device 1) and is bicontinuous in the PBDB-T:IEICO = 1:0.7 film (device 2). [87] According to the recombination mechanism in BHJ film, a vertical stratification network is detrimental to the hole transport and a bicontinuous network is favorable for the hole transport. Therefore, the perovskite solar cell with a bicontinuous HTL shows a higher PCE of 15.47%.…”
Section: Htlmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, according to the rules of energy level alignment and complementary absorption, an integrated two photoactive layer concept made by depositing a low-bandgap organic bulk-heterojunction (BHJ) layer on perovskite was proposed to extend pero-SCs' photoresponse. [25][26][27][28][29] Yang et al demonstrated an efficient integrated solar cell (ISC) by simply depositing an organic BHJ film onto MAPbI 3−x Cl x ; this achieved an additional 1.9 mA cm −2 photocurrent density increase. [29] Following the energy level matching principle, Jen et al integrated a porphyrin-derivative donor-based BHJ film with MAPbI 3 , thus extending the photoresponse to 900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Tan et al tuned the donor/acceptor weight ratios of BHJ film to enhance their charge transporting ability, and the J sc of the resultant ISC was successfully increased from 21.82 to 23.11 mA cm −2 . [27] Nevertheless, most ISCs generally exhibit a weak photocurrent contribution within 10% and are accompanied by a seriously deteriorated fill factor (FF). These behaviors indicate that the generated carriers in organic BHJ films are not sufficiently collected due to considerable charge carrier recombination in them or at the interface close to BHJ film.…”
Section: Introductionmentioning
confidence: 99%